Comparison of CaO-NPs and Chicken Eggshell-Derived CaO in the Production of Biodiesel from Schinziophyton rautanenii (Mongongo) Nut Oil. (27th February 2021) - Mmusi, Keene Carlvin; Odisitse, Sebusi; Nareetsile, Florence
Abstract : The ever-increasing population growth and economic developments have heightened demand for energy. This has resulted in depletion and ever-rising prices of petroleum diesel, thus increasing environmental degradation. These complications have motivated this study for the search of an alternative eco-friendly and renewable source of energy such as biodiesel. Biodiesel has been found to be a potential alternative fuel for diesel. Biodiesel was produced by transesterification reaction of Schinziophyton rautanenii (mongongo) nut oil in the presence of a base heterogeneous catalyst: CaO derived from eggshell ash and synthesised CaO-nanoparticles (CaO-NPs). The catalysts were calcined at a temperature of 800°C for 3 h and characterized by scanning electron microscope-energy dispersive X-ray (SEM-EDX) where both catalysts showed agglomerated particles and high elemental composition of Ca and O. Powder X-ray diffraction (XRD) showed that CaO was present in both catalysts, and the average crystalline size obtained was 42 and 50 nm for CaO-NPs and eggshell ash, respectively. Fourier transmission infrared (FTIR) spectrometer showed absorption bands of CaO in both catalysts which were at 875 and 713.46 cm −1 for CaO-NPs and eggshell ash, respectively. The analysis of mongongo nut oil (MNO) and mongongo methyl esters (MMEs) was done according to the European biodiesel specification (EN 1421) and American Society for Testing and Materials (ASTM D675). Statistically, there was no significant difference between CaO-NPs and eggshell in terms of optimum yield (P > 0.05 ) using a sample t -test. However, in terms of catalyst loading, the eggshell was a better catalyst as it required a low catalyst load to obtain an optimum yield of 83% at 6 wt.% compared to CaO-NPs with an optimum yield of 85% at 12 wt.%. The reactions were all performed at constant reaction conditions of 9 : 1 methanol to oil ratio, 3 h reaction time, and 65°C reaction temperature.